The Efficacy of Addition of Atomoxetine to Speech Therapy on the Stuttering Severity of Children Aged 4-12 Years; a Double-Blind Controlled Randomized Clinical Trial - Ahmadabadi, Farzad; Motamedi , Abdullah; zahed, ghazal; motamedi, Akram; Shahriari, Farshid; Pourfarzi, Farhad; Jafari, Narjes; Hosseini, Mohammad Mehdi; Hosseini, Mohammad Mehdi (Iranian Journal of Child Neurology, 2022)
Objectives Stuttering is a common problem at all ages and it is thus required to treat this problem since childhood. Atomoxetine is currently used for the treatment of attention deficit hyperactivity disorder (ADHD) and can also be effective for the treatment of stuttering due to its selective inhibition of norepinephrine reuptake and dopaminergic properties. Therefore, this randomized clinical trial (RCT) aimed to evaluate the effect of Atomoxetine on children’s stuttering. Materials & Methods Children aged 4–12 years, diagnosed with stuttering, who referred to pediatric neurology clinic, were randomly divided into experimental (N=50) and control (N=50) groups. One group received atomoxetine plus speech therapy and the other group only speech therapy. Both groups completed the Stuttering Severity Questionnaire (SSI4) at baseline (on the first visit) and three months after the intervention. Results Most (67%) were boy; 24% aged <60mo,46% 60–95mo,and 30% >95mo. About half (52%) had a positive family history of stuttering. Stuttering severity was highest at ages of 60–95mo, in left–handed children,those who used formula,and those who felt insecure in the family; but was not different based on child’s sex, concomitant ADHD, multilingualism, facial or movement tics, based on sleeping hours, and using teats. Mean stuttering severity reduced in both groups (P<.001) with a greater decrease in the experimental group, compared to the control group (P=.011). Conclusion Atomoxetine,plus speech therapy,is effective for the treatment of children’s stuttering and can be used as a complementary treatment strategy in these patients.